The Study of the state of soil cover of the coastal zones of the Caspian Sea, subject to the influence of climatic and anthropogenic factors - Aliyeva, N T; Mammadova, R I; Ibadova, S Y; Abdullayeva, K S; Huseynova, M A (IOP conference series. Earth and environmental science, 2023)
This article is dedicated to research of climate impact change and human activity on ecosystems. It is expressed as metals which is called heavy pollution. It covers the coastal territory of northwestern regions of Apsheron. Pollution in the coastal regions of the Caspian Sea with toxic substances, is of great concern, periodic studies of these zones for the presence of heavy metals are necessary. For the first time, a comparative analysis of the content of heavy metals in the territories of the northwestern part of the Absheron was carried out and the hypothetical reasons for their accumulation were presented. The studied soils in the northwestern part of the peninsula were grouped the degree of the density of heavy metals. Zinc (78.62 mg/kg, at a depth of 0–20 sm) copper and cadmium (23.65 mg/kg and 0.92 mg/kg at a depth of 0–20 sm). The concentration of zinc and copper in the northwestern direction of Apsheron by 1.18 and 1.57 times, compared with the allowable norms for clarks. Under the impact of flooding of coastal zones by the waters of the Caspian Sea, the average content of heavy metals, Ni, Cd, Pb in flooded soils at a depth of 0-100 sm increased by 1.7 times.